Calculative and affective commitment - the case study of the best polish employer "gaz transmission operator" - Lewicka, Dagmara; Rakowska, Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The purpose of the article is to identify organisational factors influencing the calculative and affective commitment of employees occupying different positions in an organisation. The research was conducted on a group of 397 employees of Gas Transmission Operator GAZ-SYSTEM S.A. consisting of operational, specialist and management employees1. The authors’ choice of the analysed organisation was based on the excellent performance of the organisation in the area of building the organisational commitment. On the basis of the research results, one may conclude that the calculative commitment in the organisations is largely stimulated by the following factors: the economic work conditions, justice in the organisation and development opportunities while the affective commitment is mainly dependent on the perceived support from the organisation. In addition, the research confirmed the existence of differences in factors influencing the intensity of both types of commitment in the analysed employee groups, differentiated both in terms of their positions and type of work in the organisation
Argumenta Oeconomica, 2017, Nr 2 (39), s. 213-237
Keywords: calculative commitment; affective commitment; case study